Sistema Morya Laptevykh i Prilegayushchikh Morey Arktiki : Sovremennoye Sostoyaniye i Istoriya Razvitiya = System of the Laptev Sea and the Adjacent Arctic Seas : Modern Environments and Past Environments (in Russian, with Engl. Abstracts) - Kassens, Kh.; Lisitzin, A. P.; Tide, J.; Polyakova, Ye. I.; TImokhov, L. A.; Frolov, I. E. (Izdat. Moskovskogo Universiteta, 2009)
Results of the 15-years joint Russian-German multidisciplinary researches in the Arctic are represented in this monograph. Data were obtained during numerous marine and terrestrial expeditions, all-year-round measurements and observations. On the basis of modern research methods, including satellite observations, radiocarbon (AMS14C) dating of the Arctic Sea sediments, isotope, biochemical and other methods, the authors obtained new unique records. In chapters of this monograph the latest data concerning modern sedimentation processes in the Arctic seas, modern hydrological, sea-ice and hydrobiological processes, evolution of the permafrost and paleoenvironments in the seas and the adjacent terrestrial areas are discussed.